Sex Differences in Physical Activity and Its Association With Cardiac Death and All-Cause Mortality in Patients With Implantable Cardioverter-Defibrillators - Li, Xiaoyao; Xue, Xiaodi; Sun, Xuerong; Zhao, Shuang; Chen, Keping; Hua, Wei; Su, Yangang; Yang, Jiefu; Liang, Zhaoguang; Xu, Wei; Li, Zeyi; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2020)
Objective: To clarify the impact of sex on physical activity (PA) levels among patients with implantable cardioverter-defibrillators/cardiac resynchronization therapy defibrillators (ICD/CRT-D) and its association with cardiac death and all-cause mortality. Methods: Overall, data of 820 patients with ICD/CRT-D from the SUMMIT registry were retrospectively analyzed. Baseline PA from 30 to 60 days after device implantation was measured using Biotronik accelerometer sensors. The primary and secondary endpoints were cardiac death and all-cause mortality, respectively. Results: Baseline PA levels were significantly higher in male patients than in female patients (11.40 ± 5.83% vs. 9.93 ± 5.49%, P = 0.001). Males had higher predictive PA cut-off values for cardiac death (11.16 vs. 7.15%) and all-cause mortality (11.33 vs. 7.17%). During the median follow-up time of 75.7 ± 29.1 months, patients with baseline PA<cut-off values had higher cumulative incidence of cardiac death and all-cause mortality in both males and females. At a PA level between the cut-off values of males and females, males had a higher risk of cardiac death (hazard ratio = 4.952; 95%CI = 1.055-23.245, P = 0.043) and all-cause mortality (hazard ratio = 2.432; 95%CI = 1.095-5.402, P = 0.029). Conclusions: Males had higher predictive PA cut-off values for cardiac death and all-cause mortality in patients with ICD/CRT-D. Sex should be considered as an important contributing factor when deciding for PA targets.